Managing Digital Records in Africa (Taylor & Francis, 2023)
Managing Digital Records in Africa draws on the research work of the InterPARES Trust (ITrust) project that investigated interrelated archival issues focusing on legal analysis, infrastructure, trust, authentication, and education within the African context. This research-focused book provides a legal analysis and systematic assessment of how African institutions manage digital records in four countries (i.e., Botswana, Kenya, South Africa, and Zimbabwe). It also examines the extent to which records are managed using Internet-based applications, trust in such records, and digital record authentication to support the auditing process. Finally, it provides a curriculum analysis in digital records at institutions of higher learning in 38 African countries. The book's case studies illustrate the threads of discussion, which span the ITrust domains of legislation, infrastructure, authentication, trust, and education in archives and records management. The book can be used as a premier reference source by private and public organizations, researchers, educators, archivists, records managers, and postgraduate students to make informed decisions about digital records, records management systems, cloud-based services, authenticating records, and identifying universities on the continent that offer archival programmes. The book may also find expression to practitioners in other fields such as law and auditing.
English
Keywords: African history; IT, Internet & electronic resources in libraries; Library & information services; Library, archive & information management; African history; Library, archive & information management; Internet & electronic resources in libraries; library & information services